2018
DOI: 10.1002/ets2.12176
|View full text |Cite
|
Sign up to set email alerts
|

College Access Program Alumni Reflect on Their Experiences in the Program and Its Impact on Their Skills and College Outcomes

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the results of the PUPP evaluation indicated that: a) alumni felt that the arts and cultural events they attended as a PUPP Scholar enabled them to engage in discussions about theatrical performances or other arts or cultural works with their peers in college; and b) empowered them to succeed by helping them develop their cultural knowledge, which helped to ease their transition into college and made them more well-rounded individuals (Millett & Kevelson, 2018a). These findings suggest that arts and cultural events exposure may help alumni to feel that they belong in college, even in an elite environment, just as much as those raised in more affluent homes (Bourdieu, 1986;Coleman, 1988;Kisida et al, 2014;Millett, Saunders, & Kevelson, 2018). The implication is that the cultural experiences offered by PUPP enable an expansion of students' worldviews, an outcome that is supported by recent research .…”
Section: Study Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the results of the PUPP evaluation indicated that: a) alumni felt that the arts and cultural events they attended as a PUPP Scholar enabled them to engage in discussions about theatrical performances or other arts or cultural works with their peers in college; and b) empowered them to succeed by helping them develop their cultural knowledge, which helped to ease their transition into college and made them more well-rounded individuals (Millett & Kevelson, 2018a). These findings suggest that arts and cultural events exposure may help alumni to feel that they belong in college, even in an elite environment, just as much as those raised in more affluent homes (Bourdieu, 1986;Coleman, 1988;Kisida et al, 2014;Millett, Saunders, & Kevelson, 2018). The implication is that the cultural experiences offered by PUPP enable an expansion of students' worldviews, an outcome that is supported by recent research .…”
Section: Study Limitationsmentioning
confidence: 97%
“…College access programs like PUPP, which provide high school students access to arts and cultural events, presuppose that their students may not have access to the requisite social and cultural capital these types of opportunities provide in their familial or community networks and will be more "college-ready" after exposure to said events (Musoba & Baez, 2009). In other words, exposure to arts and cultural events helps participants to "code-switch" and to feel that they belong in college, even in an elite environment, just as much as those raised in more affluent homes (Bourdieu, 1986;Coleman, 1988;Kisida et al, 2014;Millett, Saunders, & Kevelson, 2018). The implication is that the cultural experiences offered by PUPP enable an expansion of students' worldviews, an outcome that is supported by recent research (Kisida et al, 2014).…”
mentioning
confidence: 99%
“…Although the survey sample and focus group participants may not be representative of the entire PUPP alumni population, respondent alumni's self‐reported answers provide insights into the PUPP experience during high school and in the post‐PUPP period (see Millett & Kevelson, ). See the Alumni Survey and focus group report by Millett, Saunders, and Kevelson () for a detailed account of the methodology and findings for each survey, including response rates.…”
Section: Evaluation Overviewmentioning
confidence: 99%
“…They also describe scholar and alumni experiences in PUPP activities as well as their perceptions of the program's impacts on themselves and, among current PUPP scholars, on their families. Note that the PUPP Scholar Survey report (Millett & Kevelson, ) and Alumni Survey report (Millett et al, ) provide detailed accounts of the findings from all items on each survey, along with graphs and charts depicting major findings.…”
Section: Evaluation Findingsmentioning
confidence: 99%
See 1 more Smart Citation